Risk factors and outcomes of COVID‐19 in New York City; a retrospective cohort study. Issue 2 (13th August 2020) - van Gerwen, Maaike; Alsen, Mathilda; Little, Christine; Barlow, Joshua; Genden, Eric; Naymagon, Leonard; Tremblay, Douglas
Abstract: Coronavirus disease 2019 (COVID‐19) is a global pandemic and information on risk factors for worse prognosis is needed to accurately identify patients at risk and potentially provide insight into therapeutic options. In this retrospective cohort study, including 3703 patients with laboratory confirmed COVID‐19, we identified risk factors associated with all‐cause mortality, need for hospitalization and mechanical ventilation. Male gender was independently associated with increased risk of hospitalization (adjusted odds ratio [ORadj ]: 1.62; 95% confidence interval [95% CI]: 1.38‐1.91)), mechanical ventilation (ORadj : 1.35; 95% CI: 1.08‐1.69) and death (ORadj : 1.46; 95% CI: 1.17‐1.82). Patients > 60 years had higher risk of hospitalization (ORadj : 5.47; 95% CI: 4.29‐6.96), mechanical ventilation (ORadj : 3.26; 95% CI: 2.08‐5.11) and death (ORadj : 13.04; 95% CI: 6.25‐27.24). Congestive heart failure (ORadj: 1.47; 95% CI: 1.06‐2.02) and dementia (ORadj : 2.03; 95% CI: 1.46‐2.83) were associated with increased odds of death, as well as the presence of more than two comorbidities (ORadj : 1.90; 95% CI: 1.35‐2.68). Patients with COVID‐19 of older age, male gender, or having more than two comorbidities are at higher risk of hospitalization, mechanical ventilation and death, and should therefore be closely monitored. Highlights: Older age and male gender are the main risk factors for worse outcome, including death, in COVID‐19 positive patients. Diabetes and congestive heart failure are associated with increased risk of mechanical ventilation and death, as is having more than two comorbidities. Dementia is a risk factor for hospitalization and death in COVID‐19 patients therefore warranting increased monitoring of this patient population. Former smokers are less likely to be hospitalized than never and current smokers.